Prevalence of family planning practice and its determinants among women in rural areas in Pankshin district, Plateau State, Nigeria - Piritmwa, Shemu Lilibert (2021)
Family planning programme is a strategy to address issues on high fertility and mortality of mother and child. In rural areas where women are disadvantaged and family planning prevalence is relatively low as compared to urban areas, it is imperative to study the determining factors that influence family planning practice among women. A cross-sectional study using a simple random sampling method was conducted in Pankshin district in Plateau State, Nigeria, from October to December 2019. A validated self-administered questionnaire was used in data collection from 302 respondents who were rural women aged 18-49 years old using the simple random sampling method. The dependent variable in this study was ‘family planning practice” and the independent variables were individual characteristics, interpersonal characteristics and organization characteristics. Simple and multiple logistic regression were used to investigate the determinants of family planning practice. Among 302 respondents, the prevalence of family planning practices was 48.3%. The most common method of family planning among respondents who had ever practised family planning was injectables (57.5%) while among those currently practising was implants (25.3%). Majority of the respondents were aged 29-39 (40.4%). The determinants of family planning practice were age, those within the age group 29-39 and 40-49 years old were more likely to practice family planning as compared to those within younger age groups (AOR=4.373, 95% CI: 2.197-8.703, p<0.001; AOR=5.862, 95% CI: 2.522-13.625, p<0.001). Those who had discussed family planning with their partners (AOR=9.192, 95% CI: 4.356-19.400, p<0.001) and respondents who had gained the approval of their partners (AOR=2.791, 95% CI: 1.329-5.862, P=0.007). The prevalence of family planning in this study was high as compared to other results of studies in rural areas. Age, discussion with partners and partners approval are important predictors. More efforts need to be made to gain partners support in order to improve family planning practice especially among the young couples.